Lo más humano de la filosofía: la filosofía como modo de vida en las Cartas a Lucilio, de Séneca - Yepes Muñoz, Wilfer Alexis (Universidad de San Buenaventura - Cali, 2017)
In this article, the philosophy is recovered as a mode of life in Séneca’s Letters to Lucilius. The proposal is updated Sénecan therefore a crisis situation that dehumanizes the colamus humanitatem –cultivating humanity–. Existence is authentic as the man looming in a duality as a double opportunity to humanization: the body as a sign of a soul requires virtue, temperance and courage before a consumer logic that eludes our vital indigence.